Nuclear DNA content determination in Characiformes fish (Teleostei, Ostariophysi) from the Neotropical region - Carvalho, Margarida Lima; Oliveira, Claudio [UNESP]; Navarrete, Maria Clara; Froehlich, Otávio; Foresti, Fausto [UNESP] (Sociedade Brasileira de Genética, 2002)
In the present study, nuclear DNA content was analyzed in 53 species of Characiformes fish from the Neotropical region. Diploid number ranged from 2n = 48 in Astyanax fasciatus, Gymnocorymbus ternetzi and Hyphessobrycon griemi to 2n = 102 in Potamorhina squamoralevis, with a modal number of 54 chromosomes. Nuclear DNA content ranged from 1.70 ± 0.04 pg of DNA per diploid nucleus in Acestrorhynchus pantaneiro to 3.94 ± 0.09 pg in Tetragonopterus chalceus. A general analysis showed a mean value of 2.9 pg of DNA per diploid nucleus. Very similar DNA content values were observed in the species of the family Cynodontidae which showed a variation of 3% between the two genera studied. Small variations were observed between populations of Gymnocorymbus ternetzi, Astyanax fasciatus and Moenkhausia sanctaefilomenae (Characidae, Tetragonopterinae). The subfamilies Tetragonopterinae and Acestrorhynchinae (Characidae) presented the widest range, about 96%. Even in those families in which diploid number and karyotypic formulae were conserved such as the families Anostomidae, Curimatidae, and Prochilodontidae, episodes leading to losses or gains of genetic material became fixed in their evolutionary history.
Keywords: nuclear DNA; DNA content; chromosome; fish; evolution